Macrophage-Mediated Tissue Vascularization: Similarities and Differences Between Cornea and Skin - Hadrian, Karina; Willenborg, Sebastian; Bock, Felix; Cursiefen, Claus; Eming, Sabine A.; Hos, Deniz (Frontiers in Immunology, 2021)
Macrophages are critical mediators of tissue vascularization both in health and disease. In multiple tissues, macrophages have been identified as important regulators of both blood and lymphatic vessel growth, specifically following tissue injury and in pathological inflammatory responses. In development, macrophages have also been implicated in limiting vascular growth. Hence, macrophages provide an important therapeutic target to modulate tissue vascularization in the clinic. However, the molecular mechanisms how macrophages mediate tissue vascularization are still not entirely resolved. Furthermore, mechanisms might also vary among different tissues. Here we review the role of macrophages in tissue vascularization with a focus on their role in blood and lymphatic vessel formation in the barrier tissues cornea and skin. Comparing mechanisms of macrophage-mediated hem- and lymphangiogenesis in the angiogenically privileged cornea and the physiologically vascularized skin provides an opportunity to highlight similarities but also tissue-specific differences, and to understand how macrophage-mediated hem- and lymphangiogenesis can be exploited for the treatment in disease, including corneal wound healing after injury, graft rejection after corneal transplantation or pathological vascularization of the skin.